Pendampingan Penerapan Student Centered Learning dalam Meningkatkan Minat Belajar Bahasa Arab siswa Prathom di Sekolah Cho-Airong Narathiwat Thailand - Asviatul; Naura Fikroh Sadidah (Transformative Service Journal, 2025)
This community service activity was realized through a learning assistance program focused on increasing students' interest in learning Arabic. The program was implemented at Ban-Choairong Elementary School, located in Choairong Village, Narathiwat Province, Thailand. The school faces major challenges, such as low literacy levels and reduced memory retention among students. To address these issues, the author conducted a three-month program using a learning-through-play approach. The main goal of the program was to improve the quality of education through interactive teaching methods. In addition to assisting students in their learning, the author also provided training for teachers to help them implement more effective and creative teaching strategies. The stages of the program implementation included: (1) Coordination with the Narathiwat Provincial Education Office, (2) Coordination meetings with the school principal and teachers, (3) Determination of the program's direction, (4) Implementation of the learning assistance activities, (5) Evaluation, and (6) Preparation of reports and publication. The results of this program were quite significant. First, students showed increased interest in reading, writing, and memorizing Arabic vocabulary (mufradat). Second, students' motivation improved, as seen in their willingness to read Arabic sentences correctly and attend additional classes during holidays. Third, teachers became more creative in their teaching, evidenced by the students' improved focus and reduced tendency to play during lessons.